Chemical abundances and small-scale gas kinematics in the local star-forming galaxy NGC 2366 - Yarovova, Anastasiya D.; Gerasimov, Ivan S; Egorov, Oleg; Moiseev, Alexei V; Vasiliev, Konstantin I; Lozinskaya, Tatiana A (Monthly notices of the Royal Astronomical Society, 2025)
We present a detailed spectroscopic study of ionized gas in the nearby ($D\sim 3.3$ Mpc) dwarf galaxy NGC 2366, a local analogue of Green Pea galaxies, based on observations with the SCORPIO-2 instrument at the Russian 6-m BTA telescope. Using scanning Fabry-Perot interferometry and long-slit spectroscopy, we examine the gas kinematics, excitation mechanisms and chemical abundances across the disc of NGC 2366, including its prominent starburst region Mrk 71 and the companion region NGC 2363. We identified 20 regions with locally elevated H $\alpha$ velocity dispersion, only four of which correspond to known high-energy sources. We argue that one of the remaining objects can be a previously unidentified Wolf-Rayet star and two supernova remnants. For 15 H ii regions, we measure electron temperatures, oxygen and nitrogen abundances via the ‘direct’ $T_e$ method, with $12 + \log (\mathrm{O}/\mathrm{H})$ ranging from 7.6 to 8.0 in most of the regions. We show that Mrk 71 has higher oxygen abundance compared to the other H ii regions in the galaxy, contrary to the previous indirect estimates suggesting flat gradient throughout the galaxy. Together with the localized spatial variations of metallicity in the area, it is indicative of metal enrichment by the outflow from the super star cluster in the centre of Mrk 71.